(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The issue of funds that have no specific owner has occupied a wide area of research by Twelver Shiite scholars, because of its great importance, especially as it is closely related to the issue of the return of funds held by countries, governments and banks, as most of them said that it is what is called by the scholars of jurisprudence the term (unknown owner), and in the subject of the research here we try to shed light on their evidence on the issue and how they went to say it, indicating what is unknown owner and its difference from the initial permissibility and the snapshot, and what is the legitimate perception on which they based their statement, and how they divided the narratives contained in his ruling, and fuck that they divided it into four sections and according to the likelihood of diagnosing its owner and that he was unknown person and self, and then what was the ruling of the money that is seized in its details, noting that I mentioned the views of the most prominent former and contemporary scientists trying to indicate what they wanted from their evidence that there were thum, trying to discuss some of them, and they came up with a way.